2021
DOI: 10.35627/2219-5238/2021-335-2-15-21
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Using Interactive Panels in the Learning Process on the Main Parameters of the Indoor School Environment

Abstract: Summary. Introduction: Active introduction of electronic learning tools in educational institutions poses new health risks to school-age children. Creating a modern and secure digital educational environment requires constant monitoring of the conditions and modes of use of new electronic tools, the diversity of which is changing rapidly. The purpose of this work was to assess certain parameters of indoor school environment influenced by the use of interactive panels (IPs), an e-learning tool of the latest gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 16 publications
0
0
0
Order By: Relevance
“…This indicates the need to justify the hygienic requirements for the information supplied to the IP screen (contrast, clarity, color, font, etc. ); as well as constant monitoring and optimization of the microclimate in classes with IP use taken in dynamics [20].…”
Section: __________________________mentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates the need to justify the hygienic requirements for the information supplied to the IP screen (contrast, clarity, color, font, etc. ); as well as constant monitoring and optimization of the microclimate in classes with IP use taken in dynamics [20].…”
Section: __________________________mentioning
confidence: 99%
“…Previous studies have reported several complaints about health deterioration; general and visual fatigue of schoolchildren when using interactive panels in classes [19]. In addition, literature presents data indicating negative changes in the microclimate parameters in the dynamics of classes with the use of IP [20], unfavorable dynamics of the mental and visual performance of students during classes with unregulated use of IP [21]. With the accumulation of experience in the use of these electronic means in the educational process, research to study their effect on students' body remains relevant.…”
mentioning
confidence: 99%